Varstrometry for Off-nucleus and Dual Subkiloparsec Active Galactic Nuclei (VODKA): Investigating the Nature of SDSS J0823+2418 at z = 1.81, A Likely Lensed Quasar - Gross, Arran C.; Chen, Yu-Ching; Foord, Adi; Liu, Xin; Shen, Yue; Oguri, Masamune; Goulding, Andy; Hwang, Hsiang-Chih; Zakamska, Nadia L.; Ma, Yilun; Nolan, Liam (The Astrophysical journal, 2023)
Dual quasars at small physical separations are an important precursor phase of galaxy mergers, ultimately leading to the coalescence of the two supermassive black holes. Starting from a sample of dual and/or lensed quasar candidates discovered using astrometric jitter in Gaia data, we present a pilot case study of one of the most promising yet puzzling candidate dual quasars at cosmic noon ( z ∼ 1.8). Using multiwavelength imaging and spectroscopy from X-ray to radio, we test whether the SDSS J0823+2418 system is two individual quasars in a bound pair at separation ∼0.″64, or instead a single quasar being gravitationally lensed by a foreground galaxy. We find consistent flux ratios (∼1.25−1.45) between the two sources in optical, near-IR (NIR), UV, and radio, and thus similar spectral energy distributions, suggesting a strong-lensing scenario. However, differences in the radio spectral index, as well as changing X-ray fluxes, hint at either a dual quasar with otherwise nearly identical properties or perhaps lensing-based time lag of ∼3 days paired with intrinsic variability. We find with lens mass modeling that the relative NIR positions and magnitudes of the two quasars and a marginally detected central galaxy are consistent with strong lensing. Archival Sloan Digital Sky Survey spectra likewise suggest a foreground absorber via Mg ii absorption lines. We conclude that SDSS J0823+2418 is likely a lensed quasar, and therefore that the VODKA sample contains a population of these lensed systems (perhaps as high as 50%) as well as dual quasars.